Towards more ecologically relevant investigations of the impacts of microplastic pollution in freshwater ecosystems - Ockenden, Amy; Tremblay, Louis A.; Dikareva, Nadia; Simon, Kevin S. (The Science of the total environment, 2021)
Microplastic pollution is a major environmental concern and the subject of a rapidly growing body of research. Much of this research has focused on the direct effects of microplastics on single species and there is limited information on how microplastics affect different functional groups of organisms, multi-species interactions, and ecosystem processes. We focused on freshwater systems and reviewed 146 studies of microplastic effects on freshwater biota and recorded features including particle characteristics, study designs, functional types of species tested and ecotoxicological endpoints measured. Study species were categorized based on their ecosystem role/functional feeding group rather than taxonomy. We found that most studies were conducted on single species (95%) and focused on a narrow range of functional groups of organisms (mostly filter feeders, 37% of studies). Very few studies have investigated multi-species interactions and ecosystem processes. In many studies, certain characteristics of microplastics, such as polymer type were not well matched with the feeding and habitat ecology of test species, potentially reducing their ecological relevance. Median laboratory study test concentrations were 5–6 orders of magnitude higher than those reported in the field and few studies considered the effects of chemical additives in plastics (6%). We recommend that studies addressing the ecological effects of microplastics need to address neglected functional groups of organisms, design experiments to better match the ecology of test species, and increase in experimental scale and complexity to identify any indirect effects on species interactions and ecosystem processes. We suggest that examining microplastics through an ecological lens that better integrates the feeding and habitat ecology of test organisms will advance our understanding of the effects microplastics have in the environment. [Display omitted] •Laboratory study test concentrations 5–6 orders magnitude higher than in field•Key ecological groups like microbial decomposers and predators underrepresented.•Few studies investigate effects on species interactions and ecosystem processes.•Few studies test effects of chemical leachates and use natural particle controls.•Future studies should match microplastic characteristics with species ecology.